2022
DOI: 10.3390/jcs6100292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hybrid Basalt Fibres’ Length on Fresh and Mechanical Properties of Self-Compacted Ambient-Cured Geopolymer Concrete

Abstract: Recently, short basalt fibres (BFs) have been gaining considerable attention in the building materials industry because of their excellent mechanical properties and lower production cost than their counterparts. Reinforcing geopolymer composites with small volumes of fibres has been proven an efficient technique to enhance concrete's mechanical properties and durability. However, to date, no study has investigated the effect of basalt fibers’ various lengths and volume content on self-compacted geopolymer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In addition, part of the solution is spent on lubricating the BF, so the greater the amount of fiber, the greater the amount of the solution part is spent on lubricating the fibers and the more the cone settlement decreases [64,65]. In a study [66], increasing the weight content of BF from 1% to 2% led to a decrease in the slump of self-compacting geopolymer mixtures. In studies [67,68], the same picture was observed, namely, with an increase in the BF content, the workability of the mixture decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, part of the solution is spent on lubricating the BF, so the greater the amount of fiber, the greater the amount of the solution part is spent on lubricating the fibers and the more the cone settlement decreases [64,65]. In a study [66], increasing the weight content of BF from 1% to 2% led to a decrease in the slump of self-compacting geopolymer mixtures. In studies [67,68], the same picture was observed, namely, with an increase in the BF content, the workability of the mixture decreased.…”
Section: Resultsmentioning
confidence: 99%
“…It also demonstrates the lowest crack length when the three-point bending test was conducted (Wang et al, 2021d). Heweidak et al (2022) applied hybrid lengths of basalt fibres of 30 mm and 12 mm with a ratio of 3:1 and 2% binder volume in self-compacting GPC. They reported increment in compressive and indirect tensile strength by 20% (from 29.8 MPa to 35.82 MPa) and 62% (from 2.55 MPa to 4.13 MPa) respectively.…”
Section: Property Improvement Without Rca Modificationsmentioning
confidence: 95%
“…It also demonstrates the lowest crack length when the three-point bending test was conducted (Wang et al ., 2021d). Heweidak et al . (2022) applied hybrid lengths of basalt fibres of 30 mm and 12 mm with a ratio of 3:1 and 2% binder volume in self-compacting GPC.…”
Section: Rca Treatmentmentioning
confidence: 99%
“…Cementitious concrete is the fundamental foundation of the modernising globe and unequivocally one of the most synthetic utilised materials in the building sector [1]. By 2050, cement production is anticipated to increase by 12-23% due to urbanisation and infrastructure expansion [2], which will consequently increase CO 2 emissions by 4% [3].…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, cement production is anticipated to increase by 12-23% due to urbanisation and infrastructure expansion [2], which will consequently increase CO 2 emissions by 4% [3]. The World Green Building Council (WorldGBCs) urges the construction sector to adopt sustainable construction materials to approach decarbonisation by 2050 [4,5].…”
Section: Introductionmentioning
confidence: 99%